THE INFLUENCE OF ADVERTISING, DIRECT MARKETING AND EVENT EXPERIENCE ON BRAND AWARENESS AND THEIR IMPACT ON PURCHASE DECISION - Dicki Prayudi; Rusli Nugraha (Jurnal Riset Bisnis dan Manajemen, 2022)
The new model of business selling dried flower in Sukabumi has become an interesting research object to test its marketing variables. In this study, the variables used to determine the extent to which the Brand Awareness variable is formed from the Advertising variable, the direct marketing variable and the Event & Experience variable, impacted on purchasing decisions. The method used is descriptive quantitative. The model was analyzed by structural equation modeling (Structural Equation Modeling) based on components or variants (component bases) which is popular with Partial Least Square (PLS). The results show that the three variables tested significantly affect Brand Awareness, namely the Total Effect value of 0.028 for Advertising, 0.096 for Direct Marketing, and 0.0558 for Event & Experience. The conclusion in this study describes the variables that strongly support the creation of Brand Awareness in a product between Advertising, Direct Marketing and Ecent & Experience; a strengthened Event & Experience has a significant influence